Xenophobic and racially motivated crime in Belgium: exploratory spatial data analysis and spatial regressions of structural covariates. Issue 11 (2nd November 2018) - Piatkowska, Sylwia J.; Messner, Steven F.; Yang, Tse-Chuan
ABSTRACT: This study employs exploratory spatial data analysis and spatial count regression models to examine xenophobic and racially motivated crimes in Belgium between 2000 and 2012. Drawing upon recent work, we conceptualize and operationalize hate crime in multiple ways, reflecting "spaces of hate, " victimization risks, and risks adjusted for random interactions. The results reveal that hate crimes exhibit a distinct spatial imprint, which corresponds to Belgium's geographic regions. The findings also reaffirm previous research, indicating that the choice of the offset in the computation of hate crime rates is highly consequential for assessing the impact of relative group size.